Research Trends of Family Communication in Caregiving Context: A Bibliometric Mapping From 2016 to 2025 - Hanif Swastika; Reza Safitri (FAKULTAS DAKWAH UIN SALATIGA, 2026)
Despite the universal nature of family caregiving and its profound impact on family communication patterns and psychological well-being, this field remains fragmented across disciplines with limited theoretical integration and geographic disparities. This study addresses this gap by providing comprehensive landscape mapping of family communication and caregiving as an integrated field, rather than examining isolated contexts. This quantitative bibliometric analysis examines 421 Scopus-indexed articles (2016–2025) using keyword co-occurrence mapping to identify research trends in family caregiving communication by using VOSviewer software (threshold of 5 keywords). As the result, 106 keywords, 2.460 links, and 7.406 total link strength are categorized into six thematic clusters: (1) Child and Adolescent Development in Family Contexts, (2) Interpersonal Dynamics & Decision Making, (3) Social Support & Palliative Contexts, (4) Professional-Patient Interaction & Health Literacy, (5) Geriatric Caregiving & Illness Narratives, and (6) Digital Health, Migration & Crisis. The United States dominates research output (51.8%, n=218), with most prolific authors including Barkan, S.E. (n=3), Cooper, R.A. (n=3), and Goldsmith, J.V. (n=3). Meanwhile, 81% of publications originate from English-speaking countries, leaving substantial Global South populations underrepresented. While publication volume increased by 204% over the decade, with 54% (228 articles) published after 2022, analysis reveals structural asymmetries. Dementia research comprises 24% of occurrences, overshadowing emerging domains like transnational caregiving that demonstrate high citation impact. Findings are interpreted through Family Systems Theory, Relational Dialectic Theory, and Communication Privacy Management. This map identifies a critical geographic-intellectual divide and argues for a shift toward locally-grounded, longitudinal research, serving as a strategic guide for scholars and policymakers to bridge fragmented research communities and prioritize underserved caregiving settings.